E pluribus unum? Political fractionalization and deviations from the law of one price in the USA. (28th February 2021) - Antonini, Massimo; Fielding, David; Pires, Jacinta
Abstract: The magnitude of deviations from the Law of One Price (LOP) across cities depends on a number of characteristics, including language differences, distance, and other correlates of trade costs. We show that in the USA, political differences between cities are an equally important determinant of LOP deviations. LOP deviations are smaller if the cities are both strongly Democrat or both strongly Republican. These effects are of a similar order of magnitude to those of distance, and suggest that political differences represent a substantial barrier to competition.